USING TALKING STICK STRATEGY TO IMPROVE STUDENTS’ ABILITY IN QUESTIONING AND ANSWERING AND LEARNING OUTCOMES - Isnaini (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This research is motivated by a teacher-centered learning process in which teaching learning material, presenting examples, doing exercises, and tests at the end of the meeting. Researchers strive for students to be actively involved in communication in order to obtain in-depth knowledge about the material being studied. The use of the talking stick strategy is believed to improve the ability of question and answer and student learning outcomes in science. This research was a classroom action research conducted on 29 fourth grade students of SDN 002 Benai in February 2020. The instrument used was the observation sheet and learning achievement test. The results of the study in the first cycle was the ability of question and answer students by 58.3% which is enough category then the second cycle increased to 83.3% which is included in good category. The average student learning outcomes in the first cycle was 68.6 with a classical percentage of 62% having increased in the second cycle to 76.9 with a percentage of classical completeness of 89%. The conclusion of this research is the use of the talking stick strategy can improve the ability of question and answer and student learning outcomes in class IV SDN 002 Benai on science subjects.